Diplomasi Publik Thailand Melalui Industri Halal - Chandra Purnama; Neneng Konety; Akim Akim; Alwafi Ridho Subarkah (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2021)
This study aims to explain the halal industry as Thai public diplomacy. The image as Muslim friendly country become the objective of Thai government. The concept of halal and public diplomacy applied to understanding Thailand's economic development policies, especially in the manufacturing and tourism sectors. The qualitative research method uses data collection techniques based on interviews and literature studies. The researchers conducted in-depth interviews with the competent authorities and parties involved in the Thai halal industry policy. It examines the Thai government through the role of Ministry of Tourism and Sports develops Halal industry include the increasing of MICE facilities for Muslim tourists. The development of a halal certification system in Thailand in collaboration with Chulalongkorn University. The government established the Halal Industry Center on the southern border of Pattani province. Thai Agricultural Halal Standard (TAS 8400-2007) becomes the legal basis for implementing halal certification, which refers to the international halal standard - Codex. Thailand's halal food market is growing 20 percent every year and making it the sixth-ranked country as a halal food exporter. The China, 57 OIC member countries, the United States, India and Russia, are Thailand's main markets. To promote Thailand's halal tourism and industry, the government collaborates with ASEAN, Middle East countries and regularly participates in organizing exhibitions and international business forums. The Thai government's efforts have had a positive impact on national income and an increase of 10 per cent of the number of Muslim tourists every year.